Tinjauan Sistem Akuntansi Piutang dan Penerimaan Kas pada Koperasi Karyawan PT. Goodyear Tbk - Sutarti, Sutarti; Rosita, Siti Ita; Aisyah, Iis Siti (Jurnal Ilmiah Ranggagading (JIR), 2006)
Credit management at co-operative needs good accounting system and procedure to minimize risk of credit from any abuse, no-returned credit, and other risks as it has been carried out at enterprises in the form of Limited Company, CV, et cetera. The credit at Goodyear Workerâs Co-operative are acquired from material selling by credit service and being in debt by co-operative members. The finding of this study showed that credit accounting system and cash acquisition at Goodyear Workersâ Co-operative was good enough because of support by organizational structure and internal control that made separation of obvious functional responsibilities of each department and other component of control. Keywords : Credit accounting system